Do you get what you desire? Consequences of (mis) fit of desired versus actual servant leadership, and the role of context across 10 countries - Siqi Wang; Yasin Rofcanin; Mireia Las Heras; María José Bosch; Elise Marescaux (BRQ Business Research Quarterly, 2025)
This study explores how (in)congruence of desired and actual behaviors of servant leaders shape the outcomes of followers' work engagement, well-being, and turnover intentions. We underline the significance of cultural context in influencing follower outcomes and, thus, integrate a gender-cultural perspective to highlight the moderating role of gender inequality on a country level. In so doing, we postulate a strong relationship between the effects of actual/desired behaviors of servant leaders upon follower work outcomes, especially in contexts where gender inequality is high. Our results from documenting the perceptions of full-time employees (n = 2,960) across 10 countries using polynomial regression analyses show that followers' turnover intentions are lower and work engagement is higher when there is a congruence between followers' perception of servant leadership and desired servant leadership. Moreover, we found that followers' well-being is higher when actual and desired servant leadership is congruent as opposed to incongruent. In addition, the results show that the beneficial impact of congruence (as opposed to incongruence) is stronger in the cultural context where gender inequality is high. We contribute to the literature by showing the important impacts of (in)congruence between desired and actual servant leadership on followers' outcomes.
Keywords: M12; 650; Servant leadership; gender; cross-culture; work engagement; well-being